Sixth IEEE International Conference on Advanced Learning Technologies (ICALT'06)
DOI: 10.1109/icalt.2006.1652564
|View full text |Cite
|
Sign up to set email alerts
|

Performing Traditional Knowledge using a Game Engine: Communicating and Sharing Australian Aboriginal Knowledge Practices

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Using interactive sliders, the user can learn the impact of the selection of various landscape elements on ES trade-offs. While computing limitations required the use of an additional software to create photo-realistic landscape visualizations in this case study, fully featured game engines for independent low-budget game developers have become available at low price (Bishop et al, 2009;Pumpa, Wyeld, & Adkins, 2006), and could provide the next steps in such decision-support systems. For example, Unity (Unity Technologies, 2012) is a development engine for the creation of interactive 3D content with very high level of detail with regard to the visual landscape representation and high performance enabling smooth walk-throughs of virtual landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Using interactive sliders, the user can learn the impact of the selection of various landscape elements on ES trade-offs. While computing limitations required the use of an additional software to create photo-realistic landscape visualizations in this case study, fully featured game engines for independent low-budget game developers have become available at low price (Bishop et al, 2009;Pumpa, Wyeld, & Adkins, 2006), and could provide the next steps in such decision-support systems. For example, Unity (Unity Technologies, 2012) is a development engine for the creation of interactive 3D content with very high level of detail with regard to the visual landscape representation and high performance enabling smooth walk-throughs of virtual landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors identify that to ensure a smoother integration of Indigenous knowledge in to formalized Western-based curriculum, pedagogical methods and best practices for applying them have to be identified. Pumpa et al (2006) created a proof-of-concept prototype for archiving Indigenous knowledge in a digital landscape. As future work, the authors identified that the collaborative techniques used to create this content require more formalized research methodologies.…”
Section: Research Gapsmentioning
confidence: 99%
“…TGE is a ready-touse application, while additional features can be added as desired. Pumpa et al (2006) provide another example of TGE based development for communication of spatial data.…”
Section: A Collaborative Virtual Decision Environmentmentioning
confidence: 99%